P40: Rate of seed transmission of bean common mosaic virus (BCMV) in successive generations in cowpea - Dauda, N.; Ajamu, D.; Baiyeri, P.K.; Ugwuoke, K.I.; Kumar, P.L. (Association of Applied Biologists Virology Group, 2025)
This study aimed to understand the effect of genotype, time of infection, and seed morphometrics on seedborne virus infections in cowpea (Vigna unguiculata) transmission and the eventual impact of seed-borne viruses on cowpea yield compared to uninfected control. Experiments were performed using a Potyvirus species, bean common mosaic virus-blackeye (BCMV-BlCM). This virus is endemic in West Africa. Nine cowpea genotypes raised in 6-inch pots and maintained in an insect-proof screenhouse were mechanically inoculated at 7, 21, and 40 days after planting (DAP). Seeds obtained from both the inoculated and uninoculated control groups were planted, and the seedlings were examined for seedborne infection based on symptoms and RT-PCR diagnostics. All identified seed-borne plants were maintained until harvest and re-evaluated for seed transmission and the impact of seedborne viruses on cowpea yield in successive generations. In the first generation, percent BCMV seed transmission rates of 7.9, 4.6, and 44.4 were observed in genotypes RS018 inoculated at 21 DAP, RS075 (7 DAP), and RS012 (DAP). In the second generation, 35.1%, 0%, and 34.1% transmission rates were reported for the same genotypes. Significant reduction in seed yield and prolonged days to phenology was observed in seedborne plants when compared to uninfected controls. Early-stage protection against virus infection will reduce the risk of seed transmission in cowpeas.